Functional COL1A1 variants are associated with the risk of acute musculoskeletal soft tissue injuries. Issue 10 (11th February 2020) - Gibbon, Andrea; Raleigh, Stuart M.; Ribbans, William J.; Posthumus, Michael; Collins, Malcolm; September, Alison V.
Abstract: Studies have reported the association of the COL1A1 Sp1 binding site variant (rs1800012) with the risk of acute musculoskeletal soft tissue injuries. Interaction with the COL1A1 promoter variant (rs1107946) has also been proposed to modulate acute injury risk. Conversely, neither of these loci have been associated with chronic musculoskeletal soft tissue phenotypes. Therefore, the primary aim of this study involved characterizing these variants in a cohort of participants with chronic Achilles tendinopathy. Second, this study aimed to support the contribution of the rs1107946 and rs1800012 variants to the profile predisposing for acute musculoskeletal soft tissue injuries including Achilles tendon and anterior cruciate ligament (ACL) ruptures. A hypothesis‐driven association study was conducted. In total, 295 control participants, 210 participants with clinically diagnosed Achilles tendinopathy, and 72 participants with Achilles tendon ruptures recruited independently from South Africa and the United Kingdom were genotyped for the prioritized variants. In addition, a cohort including 232 control participants and 234 participants with surgically diagnosed ACL ruptures was also analyzed. Although no associations were observed in the recruited cohorts, the rare rs1800012 TT genotype was associated with decreased ACL injury risk when the results from the current study were combined with that from previously published studies ( P  = .040, OR: 2.8, 95% CI: 1.0‐11.0). In addition, the G‐T (rs1107946‐rs1800012) inferred haplotype was associated with decreased risk for Achilles tendon ruptures. These results support previous observations and reiterate the heterogeneity of musculoskeletal phenlotypes whereby certain markers may be common to the predisposing profiles while others may be unique.